Kualitas Telur Ayam Ras (Gallus L.) Setelah Penyimpanan yang dilakukan Pencelupan pada Air Mendidih dan Air Kapur Sebelum Penyimpanan - Djaelani, Muhammad Anwar (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Chicken eggs are a source of animal protein that  inexpensive and easy to obtain by the Indonesian people. Eggs contain organic materials that can be easily damaged. One of the factors that led to the destruction of the eggs is long storage periode time. This study aimed to analyze the quality of chicken eggs egg’s albumin index, the size of the air cavity and eggs pH after immersion in boiling water and lime. The samples are eggs were taken on the first day. Completely randomized design was applied with 9 treatment groups: P1 stored at room temperature without treatment was observed on 7th day, P2 is stored at room temperature without treatment was observed on 14th day, P3 is stored at room temperature without treatment was observed on 21st day, P4 dipped boiling water before storage at room temperature was observed at 7th day, P5 dipped in boiling water before storage at room temperature was observed at 14th day, P6 dipped in boiling water before storage at room temperature was observed on day 21st day, P7 soaked in lime water before it is saved on room temperature was observed at 7th day, P8 soaked in lime water before being stored at room temperature was observed at 14th day, P9 soaked in lime water before being stored at room temperature was observed at 21st day. Data were analyzed using ANOVA with a significance level of 5%. The results showed all variables decrease with increasing storage periode time. Loss of quality due to the possibility of storage duration factor that causes changes in the condition of the egg.   Keywords : egg storage, albumin index, air cavity, egg’s pH